Reakcja obozu narodowego na obchody „czerwonego dnia” 1 sierpnia 1929 roku na podstawie prasy - Borecki, Kamil (Komunizm: System - Ludzie - Dokumentacja, 2023)
For the first time, the so-called “red day”, namely the anniversary of the First World War, was celebrated on August 1, 1929. As part of the celebrations, communists from around the world organised demonstrations, parades, and anti-war protests. The communists were also agitating for the Soviet Union and campaigning against a possible attack by the “imperialist” states. The 1929 celebration was meant to be big and grandiose; it was a particularly crucial day for the Communist Party of Poland which changed its management in June 1929 and wanted to show off to the Soviet government. The national camp was the political and ideological power that ruthlessly and consistently opposed Communism in Poland; Polish nationalists were following every communist activity. The press of the national camp often wrote about the plans and tactics of the Communist Party of Poland. Thus, the national camp also followed the 6th World Congress of the Comintern, during which crucial decisions regarding the Communist movement were made. The Polish nationalists knew that the Communist Party of Poland was utterly dependent on the Kremlin, through the Comintern. The national camp had a vast knowledge of the Communist movement and was trying to announce it to the Polish society, e.g. in the press. The “red day” proved a failure: displaying the weakness of the Communist Party of Poland and the lack of support for Communism among Polish society.